2018
DOI: 10.3906/bot-1707-61
|View full text |Cite
|
Sign up to set email alerts
|

Achene morphology of the genus Cota J.Gay (Asteraceae) from Turkey and its taxonomic significance

Abstract: The genus Cota J.Gay (Asteraceae, Anthemideae) consists of 49 species (including 63 taxa) worldwide. Cota species are mainly distributed in Europe (except north of Europe), North Africa, Caucasia, and Central Asia (Davis and Hedge, 1975; Oberprieler et al., 2007). In Turkey it is represented by 15 species and 22 taxa, of which 9 are endemic. The members of Cota are especially widespread in the Mediterranean and Irano-Turanian phytogeographic regions of Turkey (Özbek et al., 2011; Özbek, 2012). Cota was earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
2
9
2
Order By: Relevance
“…The importance of seed and fruit morphology in plant systematics and taxonomy has been emphasized in several studies (Dinç, Doğu, Bilgili, & Duran, 2009; Doğu, Dinç, & Pınar, 2012; Karaismailoğlu, 2015; Luqman et al, 2019; Rashid et al, 2018). Microstructural characteristics are useful in particular for taxonomically complicated families (Bona, 2013; Karaismailoğlu, 2019; Özbek, Özbek, & Vural, 2018; Ullah et al, 2019). Analysis of micromorphological characteristics can help to acquire useful data for building an evolutionary approach among different taxonomic units (Bona, 2015; Luqman et al, 2019; Özüdoğru, Akaydın, Erik, & Mummenhoff, 2016; Rashid et al, 2018; Ullah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of seed and fruit morphology in plant systematics and taxonomy has been emphasized in several studies (Dinç, Doğu, Bilgili, & Duran, 2009; Doğu, Dinç, & Pınar, 2012; Karaismailoğlu, 2015; Luqman et al, 2019; Rashid et al, 2018). Microstructural characteristics are useful in particular for taxonomically complicated families (Bona, 2013; Karaismailoğlu, 2019; Özbek, Özbek, & Vural, 2018; Ullah et al, 2019). Analysis of micromorphological characteristics can help to acquire useful data for building an evolutionary approach among different taxonomic units (Bona, 2015; Luqman et al, 2019; Özüdoğru, Akaydın, Erik, & Mummenhoff, 2016; Rashid et al, 2018; Ullah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Macromorphological achene features of the studied species are traditionally used as diagnostic characteristics (Wagenitz, 1975). Several studies showed that achene micromorphology is also useful for identification and taxonomic delimitation in different genera in Asteraceae (Bona, 2014; Candan et al, 2016; Özbek et al, 2018; Rakizadeh, Attar, & Sotoodeh, 2019; Şirin, Ertuğrul, & Uysal, 2017). The present study aims to provide relevant characteristics of the achene macro‐micromorphology and the data useful for solving taxonomic problems through scanning electron microscopy (SEM) in the studied genera.…”
Section: Introductionmentioning
confidence: 99%
“…In one study made about achene micromorhology of asteraceae, [41] recognised that achene coat ornamentation genus of Cota has reticulate-striate. In this work, achenes also was found reticulate-striate.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The micromorphological characteristics of different plant structures have always been used as complementary tools in recent taxonomical investigations, in addition to the morphological features (Abid & Qaiser, 2009; Barthlott, 1981; Zhu, Qin, & Shih, 2006). The macro and micromorphological characteristics of fruit and pappus have been widely used in systematic evolutionary studies as well as to identify the species at the various taxonomic levels in many flowering plant groups including several tribes of Asteraceae; Anthemideae, Cichorieae, Inuleae, Senecioneae, and Mutisieae (Inceer, Bal, Ceter, & Pinar, 2012; Zhang, Boufford, & Sun, 2013; Karanović, Zorić, Zlatković, Boža, & Luković, 2016; Aksu Kalmuk, Inceer, & Imamoglu, 2018; Özbek, Özbek, & Vural, 2018), and in the tribe Cardueae (Dittrich, 1985; Gavrilović et al, 2020; Ozcan, 2017, 2018; Ozcan & Akinci, 2019). Fruit characteristics such as surface sculpturing are thought to be less influenced by the pressures of environmental conditions than other morphological traits (Barthlott, 1981).…”
Section: Introductionmentioning
confidence: 99%